Impact of soil moisture content on urban tree evaporative cooling and human thermal comfort - L. Gobatti; P. M. Bach; M. Maurer; J. P. Leitão (npj Urban Sustainability)
Abstract Urban temperatures are rising, and urban trees can help mitigate the consequences of heat stress. However, the influence of water availability on the evaporative cooling efficiency of trees across diverse urban settings remains insufficiently understood. We modelled how varying soil moisture, built environment and tree amounts affect human thermal comfort. Our results show that increasing tree cover and maintaining high soil moisture through irrigation can generate areas of ‘no thermal stress’ in Zurich during an average summer day, primarily via direct soil evaporation and in less dense Local Climate Zones. In denser built environments and without enough soil moisture, achieving such thermal comfort proved more challenging. On extreme summer days, however, even extensive tree planting and full irrigation were insufficient to alleviate heat stress, indicating the need for additional adaptation strategies. Our study underscores the critical but limited role of tree planting and water management in mitigating urban heat, offering practical recommendations for green infrastructure managers.